KEMITRAAN SEKOLAH DAN DUDI DALAM MENINGKATKAN KOMPETENSI KERJA LULUSAN MELALUI PENGUATAN ETOS KERJA DI SMK - Hindarto Hindarto; Sutama Sutama; Achmad Fathoni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze school partnerships with the business and industrial world (DUDI) in improving graduates' work competencies by strengthening work ethics at Vocational High Schools (SMK) in Demak Regency. The research was motivated by the persistent gap between the competencies of vocational high school graduates and the needs of the workforce, particularly in aspects of work ethics such as discipline, responsibility, and adaptability. The study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation. The research informants included the principal, the vice principal for industrial relations, productive teachers, fieldwork instructors, industry partners, and students who had participated in industrial work practices. Data analysis employed the interactive model of Miles, Huberman, and Saldaña, which encompasses data condensation, data presentation, and conclusion drawing. The results indicate that school partnerships with DUDI are realized through fieldwork practices, curriculum synchronization, guest lecturers from industry, and graduate recruitment. Strengthening work ethics is achieved through the instillation of an industrial work culture that emphasizes discipline, responsibility, cooperation, communication, and initiative. Research findings indicate that work ethic plays a crucial role in improving students' technical and non-technical competencies and strengthening graduates' job readiness. This research underscores the importance of ongoing collaboration between schools and the industrial and business sectors (DUDI) in producing competent, character-driven graduates who are well-suited to the needs of the workforce.